Selective hydrogenation of 1,3-butadiene: Improvement of selectivity by using additives - Alves, Javier Alberto (2004)
The objective of this work is to evaluate the behavior of isoprene as an additive to improve selectivity in the selective hydrogenation of 1,3-butadiene from 1-butene-rich cuts. To this end, the liquid-phase hydrogenation of 1,3-butadiene, 1-butene and isoprene on a commercial Pd/Al2O3 catalyst of the eggshell type at 313 K was studied in a batch system. It was found that the adsorption strength of isoprene is between those of 1,3-butadiene and 1-butene. Thus, in the presence of isoprene, 1-butene concentration remains practically constant even when the liquid is almost depleted from 1,3-butadiene. The improvement of the selectivity of an industrial reactor for 1-butene purification by adding isoprene was evaluated. To this end, a kinetic model was fitted to the experimental results and a simplified model of an industrial unit was adopted. It was found that adding 1% of isoprene can reduce 1-butene losses by a factor between 1.3 and 10 for H2 partial pressures ranging 100-500 kPa, respectively.